2015
DOI: 10.1103/physreve.91.062913
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity induces emergent functional networks for synchronization

Abstract: We study the evolution of heterogeneous networks of oscillators subject to a state-dependent interconnection rule. We find that heterogeneity in the node dynamics is key in organizing the architecture of the functional emerging networks. We demonstrate that increasing heterogeneity among the nodes in state-dependent networks of phase oscillators causes a differentiation in the activation probabilities of the links. This, in turn, yields the formation of hubs associated to nodes with larger distances from the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In short, visual interaction between players was found to affect synchronisation indices, more so when natural individual motions differed largely from each other 43 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In short, visual interaction between players was found to affect synchronisation indices, more so when natural individual motions differed largely from each other 43 .…”
Section: Resultsmentioning
confidence: 91%
“…More importantly, the significant Group X Topology interaction (F (1.648, 19.779) = 3.908, p < 0.05, η 2 = 0.246) revealed that the topology effect on synchronisation was more pronounced for the less homogenous group (Group 2), with for instance the Path graph in that group producing the lowest level of synchronisation (Bonferroni post-hoc test, p < 0.01). For further details, see Supplementary Tables 5-7. In short, visual interaction between players was found to affect synchronisation indices, more so when natural individual motions differed largely from each other [43].…”
Section: Introductionmentioning
confidence: 91%
“…For example, effects of adaptive rewiring, an adaptive network growth, or evolutionary edgesnapping are studied in Refs. [GLE06,LI11a,SCA15,PAP17,DAM19]. Also the interplay of adaptivity and complex network structure such as multilayers have been only recently numerically investigated [MAK16a, KAS18, KAS19].…”
Section: The Role Of Phase Oscillator Models For Complex Dynamical Networkmentioning
confidence: 99%
“…For this reason, inhibition and anti-Hebbian coupling have been investigated in neural systems, and they have been shown to play an important role in the control of excessive synchronization and redundancy [8][9][10], and also in the context of circadian rhythms [11]. Anti-Hebbian rules have also been considered more in general in adaptive complex networks, and it has been found that they can be useful to generate features as criticality [12], dissasortativity [6], structural heterogeneity [13], bistability [14] or multistability [15].…”
Section: Introductionmentioning
confidence: 99%